2012
DOI: 10.1080/00102202.2012.663997
|View full text |Cite
|
Sign up to set email alerts
|

Large Eddy Simulation of Turbulent Combustion in a Spark-Assisted Homogenous Charge Compression Ignition Engine

Abstract: A large eddy simulation (LES) model was developed to simulate the combustion process in a spark-assisted homogeneous charge compression ignition (SACI) engine. First, an ignition and flame propagation model based on a reaction progress variable is presented. The reaction progress variable is defined based on the normalized cumulative heat release. Transport equation for the progress variable is derived where the source terms due to flame propagation and auto-ignition are modelled. The model is then applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Computational fluid dynamics (CFD) simulations have been applied to understand the SI-CAI hybrid combustion process and the causes of its CCV. Joelsson et al [22] applied large eddy simulations (LES) to investigate the SACI combustion. They found that the first stage flame propagation is mainly affected by turbulence, whereas the second stage HCCI combustion is governed by the initial temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) simulations have been applied to understand the SI-CAI hybrid combustion process and the causes of its CCV. Joelsson et al [22] applied large eddy simulations (LES) to investigate the SACI combustion. They found that the first stage flame propagation is mainly affected by turbulence, whereas the second stage HCCI combustion is governed by the initial temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Persson et al 21 experimentally found that increasing the turbulence levels could increase the flame expansion speed at both high and low residual rates, while the auto-ignition is delayed by increased turbulence at high residual rates. Joelsson et al 23 analyzed the effect of initial temperature and turbulence fields on the SACI using large eddy simulation (LES) and found that turbulence plays a significant role in the first stage SI flame propagation. Yoo et al 24 performed two-dimensional direct numerical simulations (DNS) on the effect of turbulence on SACI and found that the high-flow turbulence significantly enhances the overall combustion by inducing many deflagration waves.…”
Section: Introductionmentioning
confidence: 99%